A study on the capability of Iloilo City to sustain the rise of shopping centers - Jayobo, Maryrose S.; Nazario, Ivy L.; Olivares, Marjaneh J.; Tenefrancia, Rona M.
Executive summary - The study is bound to answer the problem about sustainability, that is, whether Iloilo City can sustain the rise of shopping centers. Every angle was taken into consideration, as to its effect on the business field. The side of the consumers was also tackled in the research. Surveys were conducted and the group also tapped several government agencies that could give data pertinent to the issue on hand. Observations were also. made and many other factors were involved. After having gone through the process, informations gathered were analyzed as to their implications and significance. Everything was geared towards the realization of the objectives set by the group. To make the group more comprehensive, as part of the analysis, several tables showing the relationship f every factor were presented. percentages, rates, and amounts were shown. After which, a conclusion was arrived at. This would first discuss the overview of the problem, then the related statistical data to strengthen the stand of the group, and the conclusion was therefore stated. In the last part of the research, recommendations were set. These concern the government since it plays a great role in the existence of the firms, and to the shopping centers so as to serve as their guide in doing business.